PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI PENDESTRIAN HOUSE CAB. KM 11 - Wina Afriani; Mukran Roni (Universitas Indo Global Mandiri, 2022)
The Influence of Product Quality and Service Quality on Consumer Satisfaction in Pedestrian House Cab. 11 km. Supervised by Mr. Drs. Mukran Roni, M.B.A. This study aimed to determine the influence of product quality and service quality towards customer satisfaction at pedestrian house cab.km 11. This was a quantitative study with 90 consumers from Pedestria House cab. Km 11 as the population. The population then were chosen by incidental sampling so 90 samples of consumers in the Pedestrian House were collected. The data were collected using questionnaire then were analyzed using multiple regression analysing using SPSS 2.5. The results showed product quality affects consumer satisfaction and service quality also affects consumer satisfaction